RATIONALIZING VACCINE INJURY COMPENSATION - Mello, Michelle M. (Bioethics, 2008)
Legislation recently adopted by the United States Congress provides producers of pandemic vaccines with near-total immunity from civil lawsuits without making individuals injured by those vaccines eligible for compensation through the Vaccine Injury Compensation Program. The unusual decision not to provide an alternative mechanism for compensation is indicative of a broader problem of inconsistency in the American approach to vaccine-injury compensation policy. Compensation policies have tended to reflect political pressures and economic considerations more than any cognizable set of principles. This article identifies a set of ethical principles bearing on the circumstances in which vaccine injuries should be compensated, both inside and outside public health emergencies. A series of possible bases for compensation rules, some grounded in utilitarianism and some nonconsequentialist, are discussed and evaluated. Principles of fairness and reasonableness are found to constitute the strongest bases. An ethically defensible compensation policy grounded in these principles would make a compensation fund available to all individuals with severe injuries and to individuals with less-severe injuries whenever the vaccination was required by law or professional duty.